Heat shock proteins (HSPs) based anti-cancer vaccines - Ciocca, Daniel Ramon (2012)
The importance of HSPs themselves in antigen presentation and cross-presentation remains controversial. Most studies agree that as part of their molecular chaperone function, HSPs can bind and present tumor associated antigens to professional antigen presenting cells through MHC class I and class II molecules, leading to the activation of anti-tumor CD8+ and CD4+ T cells. The regulation of the innate and adaptive immune responses by HSPs is still a matter of intense research. HSPs are seen as important anticancer vaccine adjuvants. They are used through different delivery systems: HSPs/antibodies, peptide/protein-HSP complexes, tumor antigen/HSP gene fusion, viral peptides/HSP complexes or gene fusion, viral proteins/bacterial HSP fusion. In preclinical models different administration routes, subcutaneous, intradermal, intramuscular or even peroral (under special conditions) can be used, and the animal toxicities are non-significant. The HSP-based vaccines can induce specific and non-specific cellular immune responses all of which are important to induce tumor rejection. In addition, the antibodies generated after vaccination are emerging as important protagonist in the antitumoral response. This response is significantly enhanced when the suppressive tumor microenvironment and the immune suppressing effector cells are blocked. Several clinical studies have been carried out and are ongoing, immunizing cancer patients with autologous tumor derived HSP-peptide complexes (HSPPCs). The most promising results have been observed in patients with melanoma and renal clear cell cancer without advanced disease. There are clinical trials with HSP-based anticancer vaccines other than with HSPPCs (including patients with non-Hodgkin lymphoma, high-grade transitional cell carcinoma of the bladder, high-grade cervical dysplasia, etc).